The Use of Story Telling Method to Improve Young Learners’ Listening Comprehension - Erinda Aldiarti Sonda; Henri Fatkurochman; Nurkamilah Nurkamilah (SS&H: Studies in Social Sciences and Humanities, 2024)
Discovering the learning method that can improve listening skill in a foreign language/English language is essential for teachers to develop young learners’ communication skills in the beginning of learning language. Several studies had been conducted to investigate teaching method especially storytelling method that can develop listening comprehension. However, a lot of teachers implement conventional method (memorization) to teach English young learner in the beginning of learning language. The current study fills this gap by examining the use of storytelling method in developing learners’ listening comprehension as a start to learn foreign language. The base allegation of this study is that storytelling method can improve the young learners’ listening comprehension. Classroom Action Research were implemented in this study, by observing, planning, treating, re-observing, and reflecting respectively this research conducted. Observing and planning were conducted in pre-investigation until find the problem. The first observation found that there are several young English language learners have under average listening comprehension, they were treated using storytelling method on two meeting and gave them 1 test. The re-observation conducted through observing the differences pre and after treatment using observation sheet and listening test. The result findings that storytelling method plays an essential role in shaping young learners listening achievement. Furthermore, this method can build an effective classroom atmosphere that can encourage students be active in learning process. This study provides beneficial insight for English language teacher on how storytelling method can develop young learners listening comprehension which can help a lot in the beginning learning foreign language. However, to improve our knowledge of listening comprehension and storytelling method, more research is suggested to examine other variables and research participant and repeat the study in various contexts.